The Role of The Transportation and The Logistics' Sector In Achieving The Economic Development In The Saudi Arabia Kingdom and Its Challenges For The Period 2016-2021 - al-Mashhadani, Ban (The Gulf Economist, 2023)
There are challenges facing the transportation system in the logistics services field and their impact on the economic development in the Saudi Arabia Kingdom represented by the customs clearance procedures, regulations and laws that prevent the flows of foreign investments into this logistical activity. As the ranking of the logistics, performance index in the Saudi Arabia Kingdom declined from 52 globally in 2016 to 55 globally in 2018. Freight rate index retreated from the 48th rank in the world in 2016 to the 56th rank in 2018, the infrastructure index declined from the 40th rank in the world in 2016 to the 43rd rank in the world in 2018. This indicates that the determinants of the logistics' sector which includes the infrastructure index, the customs index, and the freight rate index stands up in front of them administrative and organizational challenges that hinder the development of logistics services. Therefore we see that the development of the logistics' sector will lead to achieve high quality in global logistical performance indicators. One of the most important recommendations presented in the study is the improvement of customs procedures through the implementation of additional improvement standards to reduce customs release times in seaports